The effect of football (soccer) heading on gross and fine motor control in women - Jac L. Palmer; Bert Bond; Bert Bond; Alex Woodgates; Alex Woodgates; Jacob Jack; Jacob Jack; Oliver Smail; Oliver Smail; Ryan Baker; Genevieve Williams (Frontiers in Sports and Active Living)
IntroductionHeading is an integral component of football, but concerns remain about its impact on brain health. This study examines the acute effects of heading on gross and fine motor control as a measure of the motor-cognitive function of women footballers.MethodsThe heading protocol for this study represented the typical exposure to headers experienced in the women's game: one every 10 min, for one hour, replicating a corner kick. A sample of 19 female collegiate football (soccer) players participated in two sessions: a control session, and a heading intervention. Gross motor control was assessed via measures of sway during standing balance, and fine motor control was evaluated using a precision finger grip task.ResultsResults showed no significant changes in gross motor control, based on postural sway parameters. However, significant alterations were observed in fine motor control in the tremor frequency (0–4 Hz band) of precision gripping, indicating a potential change in motor-cognitive function following the heading task.DiscussionThe findings suggest that exposure to the number and type of headers that might be performed over a typical football match does not impair standing balance, but it may affect fine motor control. Future research should look to incorporate brain imaging and electrophysiological measures to further understand the mechanisms underpinning changes in fine motor control performance after heading.